Pengaruh Kualitas Produk, Persepsi Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Kopi Kenangan Sudirman - Nurmalasari, Novita; Vitaharsa, Leonardo Indra (Journal of Economics, Bussiness and Management Issues, 2024)
This study aims to analyze the impact of product quality, price perception, and service quality on consumer purchasing decisions at the Kopi Kenangan Sudirman outlet. The population for this study comprised visitors to Kopi Kenangan, with a sample of 100 respondents selected randomly. Multiple regression analysis was employed to evaluate the influence of the independent variables on purchasing decisions. The findings reveal that product quality, price perception, and service quality collectively have a significant effect on purchasing decisions. However, when examined individually, only service quality shows a significant effect on purchasing decisions, while product quality and price perception do not exhibit significant partial effects. This study concludes that service quality is a crucial factor in influencing consumer purchasing decisions. For business owners, these results underscore the need to prioritize high-quality service in addition to ensuring reasonable product quality and pricing. Enhancing product innovation and strengthening service quality are expected to boost consumer appeal and loyalty within the food and beverage industry.